A novel αvβ3 integrin-targeted NIR-II nanoprobe for multimodal imaging-guided photothermal therapy of tumors in vivo. Issue 13 (19th March 2020) - Zhao, Meng; Ding, Jianan; Mao, Qiulian; Zhang, Yuqi; Gao, Yinjia; Ye, Shuyue; Qin, Hongni; Shi, Haibin
Abstract : A novel NIR-II probe QT-RGD consisting of a NIR-II fluorophore and two tumor-targeting cyclic-RGD peptides was reported. In vitro and in vivo studies show that it could be successfully used for multimodal NIR-II/PA/SPECT imaging and photothermal therapy of malignant tumor. Abstract : Developing novel small-molecule-based probes with both deep tissue imaging and therapeutic functions is highly significant in cancer diagnosis and treatment. Herein, we report a novel second near-infrared (NIR-II) fluorescent probe QT-RGD constructed with a NIR-II emissive organic fluorophore and two cyclic-(arginine-glycine-aspartic acid) (cRGD) peptides that can specifically bind to the tumor-associated αv β3 integrin for accurate tumor diagnosis and targeting therapy. The isotopic 125 I-labeled probe exhibited great tumor targeting ability and emitted intensive NIR-II/photoacoustic (PA)/single-photon emission computed tomography (SPECT) signals, which allows specific and sensitive multimodal visualization of tumors in vivo . More notably, this probe could also be applied for effective imaging-guided photothermal therapy (PTT) of tumors in mouse models owing to its prominent photothermal conversion efficiency and excellent photothermal stability. We thus envision that our work which unveils a combination of NIR-II/PA/SPECT imaging and PTT would offer a valuable means of improving tumor diagnostic accuracy as well as therapeutic efficacy.